2016
DOI: 10.1371/journal.pone.0157800
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Habitat Suitability Is Affected by Plant-Soil Feedback: Comparison of Field and Garden Experiment

Abstract: BackgroundField translocation experiments (i.e., the introduction of seeds or seedlings of different species into different localities) are commonly used to study habitat associations of species, as well as factors limiting species distributions and local abundances. Species planted or sown in sites where they naturally occur are expected to perform better or equally well compared to sites at which they do not occur or are rare. This, however, contrasts with the predictions of the Janzen-Connell hypothesis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…The temperature in the growth chamber differed between the cold and warm treatments and changed over the growing season following the course of temperature at the natural localities (for details, see Table ). To set the correct moisture level in the growth chambers, we used TMS5 data‐loggers to continuously measure soil moisture in the pots (TOMST Co., Hemrová, Knappová & Münzbergová ) and identified the correct level of watering to achieve soil moisture comparable to that at the localities. As a result of this calibration, the dry regime plants were watered with about 20 mL of tap water per plant applied to the trays if the soil moisture was lower than 15%.…”
Section: Methodsmentioning
confidence: 99%
“…The temperature in the growth chamber differed between the cold and warm treatments and changed over the growing season following the course of temperature at the natural localities (for details, see Table ). To set the correct moisture level in the growth chambers, we used TMS5 data‐loggers to continuously measure soil moisture in the pots (TOMST Co., Hemrová, Knappová & Münzbergová ) and identified the correct level of watering to achieve soil moisture comparable to that at the localities. As a result of this calibration, the dry regime plants were watered with about 20 mL of tap water per plant applied to the trays if the soil moisture was lower than 15%.…”
Section: Methodsmentioning
confidence: 99%
“…Moisture of the substrate in the pots was monitored by TMS3 Climatic Stations (Tomst Co., Prague, Czech Republic, www.tomst.com; Hemrová et al, 2016), one logger per treatment and species. We used seeds of six different plant species, A. lappa, Arctium tomentosum Mill., C. acanthoides, Centaurea jacea L., C. stoebe and C. vulgare.…”
Section: Experimental Designmentioning
confidence: 99%
“…All the pots also received natural rainfall (c. 130 mm over 2 months according to data from the Czech Hydrometeorological Institute; www.chmi.cz). Moisture of the substrate in the pots was monitored by TMS3 Climatic Stations (Tomst Co., Prague, Czech Republic, www.tomst.com; Hemrová et al, 2016), one logger per treatment and species. This monitoring demonstrated that moisture of the substrate in the wet regime was, on average, c. 41% higher than in the dry regime.…”
Section: Experimental Designmentioning
confidence: 99%
“…2). In the latter, especially environmental stress during early establishment is relatively severe (M€ unzbergov a 2004;Hemrov a et al 2016). In contrast, a sowing experiment in old-fields demonstrated facilitative effects of vegetation during a drier spring (Knappov a et al 2013), although in general the competitive effects prevailed.…”
Section: Discussionmentioning
confidence: 99%